1983
DOI: 10.1056/nejm198303033080902
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intermediate-Dose Methotrexate with Cranial Irradiation for the Post-Induction Treatment of Acute Lymphocytic Leukemia in Children

Abstract: We compared two regimens with respect to their ability to prolong disease-free survival in 506 children and adolescents with acute lymphocytic leukemia. All responders to induction therapy were randomized to treatment with 2400 rad of cranial irradiation plus intrathecal methotrexate or to treatment with intermediate-dose methotrexate plus intrathecal methotrexate, as prophylaxis for involvement of the central nervous system and other "sanctuary" areas. Patients were then treated with a standard maintenance re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…MDMTX. In NHR-ALL, this system of CNS prophylaxis has been shown to be more effective than 25-Gy cranial irradiation in achieving continuous remission (7,8), but its long-term effect on growth is unknown.…”
mentioning
confidence: 99%
“…MDMTX. In NHR-ALL, this system of CNS prophylaxis has been shown to be more effective than 25-Gy cranial irradiation in achieving continuous remission (7,8), but its long-term effect on growth is unknown.…”
mentioning
confidence: 99%
“…CNS involvement in non-I Hodgkin's lymphoma and acute lymphocytic leukaemia may be prevented or treated by repeated medium or high dose MTX combined with FA rescue (Freeman et al, 1983;Balis et al, 1985). Data were missing on the possibility of an adverse accumulation of FA in CSF in such protocols; in addition, as dihydrofolate reductase is present in the brain (Pollock & Kaufman, 1978), information is required on the appropriate systemic FA dose for neutralisation of excessive MTX exposure in CSF (Cohen et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Chemotherapy using methotrexate (MTX), associated (Freeman et al, 1983) or not (Balis et al, 1985) with intrathecal injections, may be effective in eradicating or preventing meningeal diseases. High dose MTX is increasingly used in place of radiotherapy (Brouwers et al, 1987), particularly for preventive purposes.…”
mentioning
confidence: 99%
“…5 8,12 The use of chemotherapy alone to prevent central nervous system leukemia has been studied by Freeman, et al, utilizing simultaneous intravenous intermediate dose methotrexate (500 mg/m2 with 1/3 as a push dose and the remaining 2/3 as a 24-hour infusion) given three times at three-week intervals following the remission of induction. 13 Others have attempted to control central nervous system disease with periodic intrathecal therapy alone with comparable results and with less toxicity to the central nervous system. [14][15][16] The randomized study by the Children's Cancer Study Group indicated clearly the inferior results obtained in a group of patients (Group IV) receiving intrathecal therapy as the sole form of prevention of central nervous system leukemia.…”
Section: Discussionmentioning
confidence: 99%